2013
DOI: 10.1167/iovs.13-12916
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Patient Matched Meibum and Tear Lipidomes

Abstract: Comparisons between tears and meibum indicate that meibum is likely to supply the majority of lipids in the tear film lipid layer. However, the observed higher mole ratio of phospholipid in tears shows that analysis of meibum alone does not provide a complete understanding of the tear film lipid composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
159
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 129 publications
(180 citation statements)
references
References 29 publications
(49 reference statements)
15
159
4
Order By: Relevance
“…Techniques are described in detail in the original study 15 , and summarized here. Tears and meibum secretions were collected from four healthy noncontact-lens wearers aged between 20 and 35 years.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Techniques are described in detail in the original study 15 , and summarized here. Tears and meibum secretions were collected from four healthy noncontact-lens wearers aged between 20 and 35 years.…”
Section: Methodsmentioning
confidence: 99%
“…A maximum 10 uL of tears was collected in a glass capillary tube placed at the edge of the lower eyelid, transferred to a microcentrifuge tube, centrifuged at low speed Following sample extraction as described previously 15 , quantification of 236 lipid molecular species was performed by chip-based tandem mass spectrometry. Lipid molecular species were normalized to total lipid and principal component analysis (PCA) was performed using MarkerView v1.2.1.1 (Sciex).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is indirect evidence that the compositions of human tear lipids diverge between people of different ethnicities. 62,68 In a study conducted by a research group in Australia, 68 it was found that human tear lipids contain 12%67% polar lipids, such as phospholipids and sphingolipids, and 4.4%60.6% of hydroxyl fatty acids. These components were not found in meibum collected from the same individuals.…”
Section: Tear Filmmentioning
confidence: 99%
“…The fact that most of this study cohort was Chinese might be the reason why there is 5 molar percent less polar lipids identified in this study when compared with the results reported by the Australian researchers. 68 The biophysical properties of tear lipids, such as dynamic interfacial behavior, elasticity, and viscosity, are crucial factors controlling tear film stability. 54,62,70,71 These properties are likely to be closely linked and strongly dependent on tear lipid composition.…”
Section: Tear Filmmentioning
confidence: 99%